2021
DOI: 10.1073/pnas.2018823118
|View full text |Cite
|
Sign up to set email alerts
|

Oviposition-promoting pars intercerebralis neurons showperiod-dependent photoperiodic changes in their firing activity in the bean bug

Abstract: Animals show photoperiodic responses in physiology and behavior to adapt to seasonal changes. Recent genetic analyses have demonstrated the significance of circadian clock genes in these responses. However, the importance of clock genes in photoperiodic responses at the cellular level and the physiological roles of the cellular responses are poorly understood. The bean bug Riptortus pedestris shows a clear photoperiodic response in its reproduction. In the bug, the pars intercerebralis (PI) is an important bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 63 publications
3
24
0
Order By: Relevance
“…An increase in extracellular glutamate is observed in brains from bean bugs reared in short photoperiod compared to those reared in long photoperiod. This change is dependent on the clock gene period ( per ), consistent with previous studies showing the importance of per in photoperiodism [ 5 , 6 ]. These results identify a new pathway by which the circadian clock could relay photoperiodic information to regulate seasonal biology.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…An increase in extracellular glutamate is observed in brains from bean bugs reared in short photoperiod compared to those reared in long photoperiod. This change is dependent on the clock gene period ( per ), consistent with previous studies showing the importance of per in photoperiodism [ 5 , 6 ]. These results identify a new pathway by which the circadian clock could relay photoperiodic information to regulate seasonal biology.…”
supporting
confidence: 89%
“…This translates into defective adaptation as the bugs are unable to enter full diapause while exposed to short photoperiod and to fully promote reproduction under long photoperiod. In a previous study, the authors showed that the electrical activity of bean bug PI neurons is responsive to photoperiod [ 6 ]. In long photoperiod, PI neurons display bursts of activity while they go silent in short photoperiod.…”
mentioning
confidence: 99%
“…However, whether and how DH31 CA neurons are regulated in response to dormancy-inducing conditions has not been elucidated. Previous studies have reported that the circadian clock system is involved in the regulation of reproductive dormancy in many insect species (4, 53, 72, 73), including D. melanogaster (27, 51, 60, 74). Therefore, we propose that, to an extent, circadian clock neurons, such as 5 th s-LNv, s-LNv, LNd, and DN1p are connected with DH31 CA neurons and modulated its activity under dormancy-inducing conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Photoperiodic control of neural activities has been reported in a few insect brain neurosecretory cells (NSCs) (Hamanaka et al, 2004; Hasebe & Shiga, 2021; Tomioka et al, 1995). In the tobacco hornworm Manduca sexta , a neuropeptide prohoracicotropic hormone (PTTH) is a primary factor in pupal diapause regulation, the cessation of which is considered to be responsible for the pupal diapause (Bowen et al, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…Some brain NSCs, which regulate reproductive diapause (Shiga & Numata, 2000), show significant differences in spike durations and spike heights between diapause‐averting and diapause‐inducing conditions (Hamanaka et al, 2004). In addition, in the bean bug Riptortus pedestris , brain NSCs essential for oviposition exhibit photoperiodic changes in firing, high firing activity being observed in photoperiodic conditions suitable for oviposition (Hasebe & Shiga, 2021). These findings imply that photoperiod‐dependent regulation of the electrophysiological properties of NSCs has a crucial role in diapause regulation.…”
Section: Introductionmentioning
confidence: 99%